Replication and virulence in pigs of the first African swine fever virus isolated in China - Dongming Zhao; Renqiang Liu; Xianfeng Zhang; Fang Li; Jingfei Wang; Jiwen Zhang; Xing Liu; Lulu Wang; Jiaoer Zhang; Xinzhou Wu; Yuntao Guan; Weiye Chen; et al. (Emerging Microbes and Infections)
African swine fever (ASF) entered China in August 2018 and rapidly spread across the entire country, severely threatening the Chinese domestic pig population, which accounts for more than 50% of the pig population worldwide. In this study, an ASFV isolate, Pig/Heilongjiang/2018 (Pig/HLJ/18), was isolated in primary porcine alveolar macrophages (PAMs) from a pig sample from an ASF outbreak farm. The isolate was characterized by using the haemadsorption (HAD) test, Western blotting and immunofluorescence, and electronic microscopy. Phylogenetic analysis of the viral p72 gene revealed that Pig/HLJ/18 belongs to Genotype II. Infectious titres of virus propagated in primary PAMs and pig marrow macrophages were as high as 107.2 HAD50/ml. Specific-pathogen-free pigs intramuscularly inoculated with different virus dosages at 103.5–106.5 HAD50 showed acute disease with fever and haemorrhagic signs. The incubation periods were 3–5 days for virus-inoculated pigs and 9 days for contact pigs. All virus-inoculated pigs died between 6–9 days post-inoculation (p.i.), and the contact pigs died between 13–14 days post-contact (p.c.). Viremia started on day 2 p.i. in inoculated pigs and on day 9 p.c. in contact pigs. Viral genomic DNA started to be detected from oral and rectal swab samples on 2–5 days p.i. in virus-inoculated pigs, and 6–10 days p.c. in contact pigs. These results indicate that Pig/HLJ/18 is highly virulent and transmissible in domestic pigs. Our study demonstrates the threat of ASFV and emphasizes the need to control and eradicate ASF in China.